Exercise Counterbalances Rho/ROCK2 Signaling Impairment in the Skeletal Muscle and Ameliorates Insulin Sensitivity in Obese Mice - Muñoz, Vitor R.; Gaspar, Rafael C.; Severino, Matheus B.; Macêdo, Ana P. A.; Simabuco, Fernando M.; Ropelle, Eduardo R.; Cintra, Dennys E.; da Silva, Adelino S. R.; Kim, Young-Bum; Pauli, José Rodrigo (Frontiers in Immunology, 2021)
Physical exercise is considered a fundamental strategy in improving insulin sensitivity and glucose uptake in skeletal muscle. However, the molecular mechanisms underlying this regulation, primarily on skeletal muscle glucose uptake, are not fully understood. Recent evidence has shown that Rho-kinase (ROCK) isoforms play a pivotal role in regulating skeletal muscle glucose uptake and systemic glucose homeostasis. The current study evaluated the effect of physical exercise on ROCK2 signaling in skeletal muscle of insulin-resistant obese animals. Physiological (ITT) and molecular analysis (immunoblotting and RT-qPCR) were performed. The contents of RhoA and ROCK2 protein were decreased in skeletal muscle of obese mice compared with control mice but restored to normal levels in response to physical exercise. The exercised animals also showed higher phosphorylation of insulin receptor substrate 1 (IRS1 Serine 632/635) and protein kinase B (Akt) in the skeletal muscle. However, phosphatase and tensin homolog (PTEN) and protein-tyrosine phosphatase-1B (PTP-1B), both of which are inhibitory regulators for insulin action, were increased in obesity but decreased after exercise. The impact of ROCK2 action on muscle insulin signaling is further underscored by the fact that impaired IRS1 and Akt phosphorylation caused by palmitate in C2C12 myotubes was entirely restored by ROCK2 overexpression. These results suggest that the exercise-induced upregulation of RhoA-ROCK2 signaling in skeletal muscle is associated with increased systemic insulin sensitivity in obese mice and further implicate that muscle ROCK2 could be a potential target for treating obesity-linked metabolic disorders.